Effect of seed treatment on germination and flavonoids diversity in accessions of butterfly pea (Clitoria ternatea) - MAKASANA, JAYANTI; PILLAI, VIPUL; SHARMA, ANJALI; DHOLAKIYA, BHARATKUMAR Z; GAJBHIYE5, NARENDRA ATMARAM; SARAVANAN, RAJU (The Indian Journal of Agricultural Sciences, 2016)
Butterfly pea (Clitoria ternatea) or aparajita is a medicinal herb with diverse medicinal properties including memory enhancing, antistress, anxiolytic, antidepressant, anticonvulsant, tranquilizing, and sedative properties. Various phytochemicals such as triterpenoids, flavonol glycosides, anthocyanins and steroids are reported in this species. Plant types with white and purple flowers are reported to occur in different regions of India. The phytochemical diversity with reference to geographical locations are not available for this species. Understanding the phytochemical diversity and characterization of genotypes are essential for commercial cultivation, conservation and future breeding programme. In the present study, we evaluated the phytochemical diversity of 19 accessions from different geographical regions from India in terms of flavonoid accumulation. Flavonoid content significantly (p < 0.05) varied in the species with geographical locations, and were in range from 1.0 ± 0.06 to 3.5 ± 0.1 mg/g of quercetin and 4.1 ± 0.08 to 8.5 ± 0.17 mg/g of kaempferol in dry leaf of C. ternatea. Highest kaempferol content was found in ODB-W; quercetin was highest in AP-B accession, while MH-T accession had the lowest kaempferol and quercetin among the accessions. Seed germination aspect of C. ternatea was studied as the plant belongs to a fabaceae family having seed coat dormancy and still there is a gap in availability of information on its seed germination. Effect of acid treatment on seed germination indicated that C. ternatea seed coat dormancy could be efficiently removed by treating with concentrated sulfuric acid for 10-15 min at 30°C.